Temporal scale-bridging of chemistry in a multiscale model: Application to reactivity of an energetic material - Leiter, Kenneth W.; Larentzos, James P.; Barnes, Brian C.; Brennan, John K.; Becker, Richard; Knap, Jaroslaw (Journal of computational physics, 2023)
A heterogeneous multiscale method (HMM) to evolve chemistry across disparate temporal scales is presented. The method directly couples a particle-based, microscale coarse-grain chemistry model to a macroscale continuum finite element model of deformation. The macroscale model obtains both the material equation-of-state and instantaneous chemical reaction rates through evaluation of the microscale model subject to distinct boundary conditions. The approach is demonstrated through several simulations of the energetic material 1,3,5-trinitrohexahydro-s-triazine (RDX) subject to slow heating, including a simulation inspired by the scaled thermal explosion (STEX) experiment. •We develop a concurrent multiscale model of a reactive energetic material.•The model incorporates a temporal scale-bridging algorithm to evolve chemistry across scales.•We use the model to simulate heating leading to chemical decomposition and deformation.•Simulations establish the model is able to capture the multiscale coupling between deformation and chemistry.